Lipid signaling pathways genes expression level in HEPG2 cells supplemented with exogenous lipid and edible bird nest (EBN) extract - Tawai, Darreen (2018)
“Caviar of the East” or better known as Edible-Bird Nest (EBN) is a highly valuable product composed from solidified salivary secretion of a few insectivorous swiftlet species. Swiftlets falls under the family Apodidae and the two main genera with the highest commercial values are Aerodramus (echolating swiftlets) and Collocalia (non-echolating swiftlets). The objective of this study is to determine the qualitative genes expression associated in lipid signalling pathways such as Acetyl-CoA acetyltransferase 2 (ACAT2), Diacylglycerol O-acyltransferase 2 (DGAT2), Low density lipoprotein receptor (LDLR), Sterol regulatory element binding transcription factor 2 (SREBP2), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), Proprotein Convertase Subtilisin/kexin type 9 (PCSK9) in HepG2 mammalian cell with or without supplementation of EBN extract and exogenous lipid. Raw EBN were manually cleaned, dried in 60°C oven and left overnight. In this project, EBN supernatant were added with acetone using 1:2 ratio and kept in -80°C for an hour. Hep G2 cells were cultured in six wells plates and each wells were treated according to Base Control, Positive Control, Negative Control, Treatment 1, Treatment 2 and Treatment 3. In this study, there are significant changes in term of genes expression with supplementation of EBN extract especially in ACAT2 and LDLR genes.